Frame by frame : a materialist aesthetics of animated cartoons - Frank, Hannah, 1984-2017 (University of California Press, 2019)
"This book examines the visual aesthetics of popular American animated cartoons. For most of the twentieth century, the making of cartoons was mechanized and standardized: thousands of drawings were inked and painted onto individual transparent celluloid sheets (called 'cels') and then photographed in succession, a labor-intensive process that was divided across scores of artists and technicians. In order to understand the art, labor, and technology of cel animation, this book analyzes cartoons frame by frame to expose hitherto unseen qualities of the image. What emerges is both a method and an original account of an art formed on the assembly line"--Provided by publisher.